Central Kurdish Operators in Role and Reference Grammar - Farzad Azizi; Payman Rezvani (Zanco Journal of Humanity Sciences)
Operator theory constructs one of the key elements of the layered structure of the clause in Role and Reference Grammar. In fact, operators make a closed class of grammatical or functional components which modify different layers of the clause. Respectively, the present operators in every layer comprise their specific sub-layers with a projection different from the structural projection. It should be mentioned that negative and illocutionary force operators are the only universal operators among others. The present paper aims to define and analyze these components in Central Kurdish Dialect (CKD); henceforth, the theoretical framework is presented according to Van Valin (2005) and Pavey (2010). Then, Mukriyani’s examples as one of the sub-dialects of CKD, which are chosen from daily interactions are studied in this frame. It is worth mentioning here that the researchers are native speakers of CKD, and their intuition plays an important role in describing and explaining the results, pointing the most important ones as: CKD’s operators appear around the syntactic structure of Nucleus in two morphological forms of prefix and suffix, which in turn, are presented in three lexical forms of modal verbs, linking verbs and phonologically null morpheme.